INVESTIGATION OF PROPERTIES OF COATINGS DEPOSITED BY DIFFERENT ARC SPRAYING METHODS - Brusylo, Y. V.; Cherepko, A. E. (Science-based technologies, 2014)
Increase in the service life and reduction in expenses for manufacture and maintenance of friction pair parts (crankshafts, inserts, bushes, etc.) of transport machinery is one of the most important problems to be solved by scientific researchers, technologists and constructors. However, in the beginning, an electric arc spraying (EAS) was only aimed at corrosion protection of welded metallic constructions, and properties of electric arc coatings for other purposes have not been studied properly yet. Therefore, implementation in industry of EAS in order to prolong the service life of parts and renew them for provision of transport enterprises with spare parts is an actual task. There have been results of comparative analysis for properties of coatings deposited by an electric arc spraying (EAS) using gas-air mixture and activated electric arc spraying (AAS) using the products of combustion of propane-air mixture. Under optimal spraying process conditions, the porosity of AAS-produced coatings is much smaller as compared to EAS: 2–4 and 9–11 %, respectively. The adhesion strength of AAS coatings is higher by 1.8–2.2 times. When developing techniques for the base roughness decrease, it is necessary to choose those techniques for pretreatment of base surfaces which provide low roughness Rz: within 5–10 mcm.